Cover Picture: Computationally Probing the Performance of Hybrid, Heterogeneous, and Homogeneous Iridium‐Based Catalysts for Water Oxidation (ChemCatChem 10/2016). Issue 10 (20th May 2016) - García‐Melchor, Max; Vilella, Laia; López, Núria; Vojvodic, Aleksandra
Abstract : The Front Cover shows a very appealing strategy for designing oxygen evolution electrocatalysts with enhanced activity. It consists of anchoring an active homogeneous complex on a solid support, thus creating a hybrid‐type of catalyst. The fundamental idea behind these combined systems is the synergy between the individual properties of its homogeneous and heterogeneous constituents, as the limitations of one are usually the main advantages of the other. In their Full Paper, M. García‐Melchor et al. show that a molecular Ir catalyst can be strongly attached to an Ir oxide surface without losing apparent activity. This work may contribute to advance towards the design of high‐performance water oxidation electrocatalysts. More information can be found in the Full Paper by M. García‐Melchor et al. onpage 1792 in Issue 10, 2016 (DOI:10.1002/cctc.201600007 ).